2002
DOI: 10.1248/cpb.50.1283
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Mediated Deacylation of Amino Acid Esters with Marked Stereoselectivity.

Abstract: Stereoselective hydrolysis of amino acid esters have attracted considerable attention in connection with understanding the origins of the stereoselectivity observed with proteolytic enzymes. In the course of our study on the enantioselective hydrolysis (deacylation) of amino acid esters with the functional molecular assemblies composed of surfactants and reactive species, we emphasized that the stereochemical control could be attained by changing the composition of the coaggregates 1-4) and regulating ionic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Moreover, the same idea reappeared in the works of e.g. Goto [84], Treat [85,86], Duan [87][88][89][90], Fulp [91], and Kashiwa and Tanimura [92,93]. However, since Chen et al revived this idea in the context of the controversy about the angular momentum decomposition, we shall refer to the generic split (167) as the "Chen et al approach".…”
Section: B the Covariant Form Of The Decompositionsmentioning
confidence: 98%
“…Moreover, the same idea reappeared in the works of e.g. Goto [84], Treat [85,86], Duan [87][88][89][90], Fulp [91], and Kashiwa and Tanimura [92,93]. However, since Chen et al revived this idea in the context of the controversy about the angular momentum decomposition, we shall refer to the generic split (167) as the "Chen et al approach".…”
Section: B the Covariant Form Of The Decompositionsmentioning
confidence: 98%
“…CDs play an important role in preorganizing the guest molecules through the hydrophobic interactions. A number of studies have reported the use of unmodified or simply modified CD monomers without metal ions for the enantioselective deacylation of chiral esters 26 27 28 29 30 31 32 . However, the cooperative enantioselective catalytic effect arising from CDs’ intramolecular interactions with coordinated metal ions have rarely been reported, and the cooperative mechanism also remains unclear.…”
mentioning
confidence: 99%
“…The value was among the largest ones which were gained by using CD-based [29][30][31] or other surfactants containing complex [49,50] as artificial mimics, and are close to those cases by using enzymes or modified enzymes [5,47,50,51], for the hydrolysis of amino acid esters or peptide esters. The hydrolysis of Boc-Lys(Boc)-ONp enantiomers promoted by CuL 1 resulted in more pronounced enantioselectivity than that of Boc-Ala-ONp, with an enantiomer selectivity of 8.8.…”
Section: Saturation Kinetics Promoted By Culmentioning
confidence: 64%
“…Fig. 2 shows the dependence of the rate constants on the CuL 1 concentration [28,29,[47][48][49]. By increasing the initial catalyst concentration from 5.0 to 100.0 M, deviation from linear increase was observed (Fig.…”
Section: Saturation Kinetics Promoted By Culmentioning
confidence: 98%
See 1 more Smart Citation